2019
DOI: 10.1021/acs.jafc.9b05849
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Qingke Liquor Aroma from Tibet

Abstract: Qingke liquor is a very famous Tibetan alcoholic beverage made from “Qingke”, hull-less highland barley, which is exclusively grown in Qinghai-Tibetan Plateau with an average altitude of 4000 m. Qingke liquor made in such an area whose quality or characteristics is a result of its geographic environment, including natural and human culture. In this study, the aroma compounds in two Qingke liquors made from highland barley grown at different elevations (QKH, high elevation, and QKL, low elevation) were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…AEDA was conducted based on the aforementioned GC-MS-O method with procedures reported in previous literatures [14][15][16]. The SDE extract were gradually diluted in the ratio of 4 (by volume) with n-hexane, followed by GC-MS-O analysis.…”
Section: Aroma Extract Dilution Analysis (Aeda)mentioning
confidence: 99%
See 2 more Smart Citations
“…AEDA was conducted based on the aforementioned GC-MS-O method with procedures reported in previous literatures [14][15][16]. The SDE extract were gradually diluted in the ratio of 4 (by volume) with n-hexane, followed by GC-MS-O analysis.…”
Section: Aroma Extract Dilution Analysis (Aeda)mentioning
confidence: 99%
“…In order to evaluate whether the key aromatic compounds were identified correctly, aroma reconstruction and omission experiments were performed according to the methods reported in the previous literatures with minor modifications [11,14,17]. The aroma reconstruction model of the SDE extract (FM1) was prepared with the 15 aromatic volatiles (except hotrienol) at concentrations measured (Table 1), where n-hexane was used as the matrix, and the final volume was 1.5 mL.…”
Section: Aroma Reconstruction and Omission Test Of Major Aroma Contrimentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that both liquors had a similar aroma profile, but the Osme values varied (Figure 1). Most of these components are well-known odorants in Baijiu [7,17,18], but 36 of them have not been reported in a previous study of xiaoqu Baijiu [13]. Among the 79 aroma compounds, 26 esters, 15 alcohols, 12 aldehydes and ketones, nine acids, six phenols, five terpenoids, four furans, and two sulfur compounds were detected in the M and T samples.…”
Section: Identification Of Aroma Compounds In Xiaoqu Baijiu Using Gc-omentioning
confidence: 89%
“…Gas chromatography-olfactometry (GC-O) was first used to study the aroma-active compounds in baijiu in 2005 [ 3 ]. Among all the aroma-active compounds identified, fatty acid esters have been proven to be the main contributors to baijiu aroma [ 3 , 4 , 5 , 6 , 7 ], exhibiting fruity and floral notes [ 3 , 4 , 5 , 6 ]. Free fatty acids and alcohols also make important aroma contributions.…”
Section: Introductionmentioning
confidence: 99%